Ketaatan Kepada Pemerintah Dalam Perspektif Perjanjian Baru - Kasieli Zebua; Mario Gani (Sekolah Tinggi Teologi Syalom Bandar Lampung, 2023)
In the New Testament, there is quite a lot of advice for Christians to submit and obey the government. Advice like this is of course still relevant today, and it is important to be explored as a guideline for Christians to be right towards the government, both towards the right government and the cruel government. But to what extent and within what limits should Christians obey the government? This study uses a literature review method with an emphasis on theological studies that aims to find truths from biblical investigations about Christian obedience to the government. From the results of the research found the teachings of the Bible about the right attitude of Christians towards the government as God's servants ordained by God. And also the limitation of obedience when the government is not in line with God's will and even against God's purpose. So that this becomes the basis for today's Christians to respond to various government regulations and policies in accordance with the truth of God's Word. Also as a basis that reflects a life that is bright and exemplary as a follower of Christ in the midst of society. Abstrak Di dalam Alkitab Perjanjian Baru cukup banyak nasihat agar orang Kristen tunduk dan taat kepada pemerintah. Nasihat semacam ini tentunya tetap relevan zaman sekarang, dan penting untuk didalami menjadi pedoman bagi orang Kristen untuk bersikap benar terhadap pemerintah, baik kepada pemerintah yang benar maupun pemerintah yang kejam. Namun sejauh mana dan dalam batas-batas apa orang Kristen harus taat kepada pemerintah? Penelitian ini menggunakan metode kajian kepustakaan dengan penekatan kajian teologis yang bertujuan untuk menemukan kebenaran-kebenaran dari penyelidikan biblikal tentang ketaatan orang Kristen kepada pemerintah. Dari hasil penelitian ditemukan ajaran Alkitab tentang sikap yang benar dari orang Kristen terhadap pemerintah sebagai hamba Allah yang ditetapkan Allah. Dan juga batasan ketaatan ketika pemerintah tidak sejalan dengan kehendak Allah bahkan menentang tujuan Allah. Sehingga hal ini menjadi dasar bagi orang Kristen masa kini menyikapi berbagai peraturan dan kebijakan pemerintah sesuai dengan kebenaran Firman Tuhan. Juga sebagai dasar yang mencerminkan kehidupan yang menjadi terang dan teladan sebagai pengikut Kristus di tengah-tengah masyarakat.